Peranan Komunikasi Persuasif Dalam Implementasi Ajaran Tri Hita Karana Pada Sekaa Truna Truni - Ida Bagus Putu Eka Suadnyana; Krisna Suksma Yogiswari (Jayapangus Press, 2020)
Sekaa Truna Truni is a youth organization which serve as a platform for youth and women in developing creativity and activity in order to form the next generation who will be able to support the construction and development of the Banjar and Pakraman toward a better future. As the voice of young container, Sekaa Truni Truni are certainly a whole is expected to implement the teachings of religious doctrine in this case Tri Hita Karana. In the teachings of Tri Hita Karana implementas required good communication between members Sekaa Truna Truni. Which is expected to create a harmonious relationship between man and his fellow (pawongan), man and nature or environment (palemaham), and man to God (parahyangan)